1976
DOI: 10.1177/001316447603600314
|View full text |Cite
|
Sign up to set email alerts
|

A Psychometric Analysis of the Ross Educational Philosophical Inventory (REPI

Abstract: This research was directed at an examination of the pyschometric properties of the Ross Educational Philosophical Inventory (REPI), an instrument designed to investigate underlying philosophical beliefs influencing teaching behaviors and policy decisions of educational administrators. The REPI claims to measure individual attitudes with respect to four philosophical systems—Idealism; Realism; Existentialism; Pragmatism. Content evaluation and second-order factor analyses resulted in the dimensionalizing of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1979
1979
1979
1979

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Maurice Villano C1973), who conducted a psychometric analysis of the REPI, concluded that the inventory did not measure the four philo sophical domains of realism, idealism, pragmatism, and existentialism as proported by its developer. In a second, more extensive, study of the properties of the REPI, R. L. Ziomek (1975) Phillips' findings revealed that although liberal arts graduates exhibited higher scores than teachers college graduates on the MTAI (higher scores on the MTAI implying a more "liberal" teacher attitude toward pupils and teaching procedures, whereas, lower scores implying a more "conservative" outlook and practice), no significant differences were found between the two categories of teachers compared at each of three teaching levels (elementary, middle and high school). Likewise, he found no significant differences among the means for the personality scores for the teacher categories analyzed at the individual levels.…”
Section: The Leede « Cook and Medley Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Maurice Villano C1973), who conducted a psychometric analysis of the REPI, concluded that the inventory did not measure the four philo sophical domains of realism, idealism, pragmatism, and existentialism as proported by its developer. In a second, more extensive, study of the properties of the REPI, R. L. Ziomek (1975) Phillips' findings revealed that although liberal arts graduates exhibited higher scores than teachers college graduates on the MTAI (higher scores on the MTAI implying a more "liberal" teacher attitude toward pupils and teaching procedures, whereas, lower scores implying a more "conservative" outlook and practice), no significant differences were found between the two categories of teachers compared at each of three teaching levels (elementary, middle and high school). Likewise, he found no significant differences among the means for the personality scores for the teacher categories analyzed at the individual levels.…”
Section: The Leede « Cook and Medley Studiesmentioning
confidence: 99%
“…The exigencies of time and testing circumstances necessi tated the utilization of the single Form C in the current study. (Ziomek, 1975) with respect to one of the four philosophical positions being measured, i.e. realism, idealism, pragmatism, and existentialism.…”
Section: -82)mentioning
confidence: 99%
“…Many "homemade" instruments have appeared in the past 40 years designed to do this. Recently, researchers at Iowa State University (Ziomek and Smith, 1980) have developed a valid and reliable device for assessing this area of attitude/belief. Ziomek (1978) has examined the relationship between philosophical attitudes and personality charac teristics.…”
Section: Much Of the Experimental Work On Which This Concept Is Basedmentioning
confidence: 99%